2014
DOI: 10.1002/smi.2616
|View full text |Cite
|
Sign up to set email alerts
|

Stressors and Coping Strategies of UK Firefighters during On‐duty Incidents

Abstract: Operational response by firefighters requires an abrupt change from rest to near-maximal physical effort and incorporates almost instant stress management that must be made during extreme heat, limited time and partial information, yet little is known about the coping strategies incorporated to manage the physiological and psychological demands associated with this environment. A sample of 22 UK firefighters took part in focus groups identifying frequently used coping techniques based upon problem-focused and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 32 publications
1
31
0
1
Order By: Relevance
“…'Social support' was quoted by all the firefighters as the best method to buffer the effects of stress. This accords with previous literature that has cited social support as a buffer for high stress levels (Haslam and Mallon 2003;Young et al 2014). Interviewees reported that there were sufficient resources within the organisation to offer social support when needed (i.e., 'organisational support').…”
Section: Theme 4: Moderatorssupporting
confidence: 86%
See 1 more Smart Citation
“…'Social support' was quoted by all the firefighters as the best method to buffer the effects of stress. This accords with previous literature that has cited social support as a buffer for high stress levels (Haslam and Mallon 2003;Young et al 2014). Interviewees reported that there were sufficient resources within the organisation to offer social support when needed (i.e., 'organisational support').…”
Section: Theme 4: Moderatorssupporting
confidence: 86%
“…Our findings suggested that all the employees felt they had adequate social support irrespective of their length of the experience, whereas Regher et al (2003) found newly recruited firefighters received more support than experienced firefighters. Moreover, alike Young et al's (2014) findings, the interviewees that had less experience particularly mentioned seeking social support from more experienced members of the watch as a way of managing distress.…”
Section: Theme 4: Moderatorsmentioning
confidence: 53%
“…The findings advocate for the use of the conservation of resources model (Hobfoll, ), suggesting that the attainment and preservation of resources were related to the achievement of resilience and posttraumatic growth. Young, Partington, Wetherell, St Clair Gibson, and Partington (this issue) sampled fire fighters in the United Kingdom utilising a qualitative methodology to investigate the coping mechanisms used by this at‐risk group. They found that peer social support and humour were beneficial strategies utilised by fire fighters as coping methods.…”
Section: Guest Editors: Ian De Terte and Christine Stephens New Zealandmentioning
confidence: 99%
“…However, clear recommendations about which kind of coping strategies to prefer are not reasonable as the effectiveness of a particular coping strategy depends on individual determinants as well as on situational circumstances (Aldwin, 2007). As an example, problem-focused approaches seem to be recommendable whenever at least parts of the situation can be controlled whereas emotionfocused strategies might be more effective to regulate emotions in uncontrollable circumstances or in the aftermath of a disaster (Jensen & Wrisberg, 2014;Young, Partington, Wetherell, St Clair Gibson, & Partington, 2014). Consistent with these aspects, the crisis managers interviewed in this study recommended that everyone is given the opportunity to find his or her own effective stress management strategies that may differ during the different disaster phases.…”
mentioning
confidence: 75%